2009
DOI: 10.1007/s11104-009-0088-9
|View full text |Cite
|
Sign up to set email alerts
|

Variation in seedling growth of 11 perennial legumes in response to phosphorus supply

Abstract: Phosphorus (P) deficiency is a major problem for Australian agriculture. Development of new perennial pasture legumes that acquire or use P more efficiently than the current major perennial pasture legume, lucerne (Medicago sativa L.), is urgent. A glasshouse experiment compared the response of ten perennial herbaceous legume species to a series of P supplies ranging from 0 to 384 µg g −1 soil, with lucerne as the control. Under low-P conditions, several legumes produced more biomass than lucerne. Four species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
66
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 28 publications
10
66
1
1
Order By: Relevance
“…Phosphorus deficiency caused reduced biomass, photosynthetic activity and nitrogen fixing ability in mungbean (Vigna aconitifolia) and mashbean (Vigna radiata) [33]. Under P deficiency conditions, genotypic variation in biomass production is evident; according to Pang et al (2010) [34], who studied in a glasshouse experiment the response of ten perennial herbaceous legume species, found that under low P conditions several legumes produced more biomass than lucerne. Nutrient deficiency may cause physiological and metabolism abnormalities in plants, which may lead to deficiency symptoms.…”
Section: Nutrient Availabilitymentioning
confidence: 99%
“…Phosphorus deficiency caused reduced biomass, photosynthetic activity and nitrogen fixing ability in mungbean (Vigna aconitifolia) and mashbean (Vigna radiata) [33]. Under P deficiency conditions, genotypic variation in biomass production is evident; according to Pang et al (2010) [34], who studied in a glasshouse experiment the response of ten perennial herbaceous legume species, found that under low P conditions several legumes produced more biomass than lucerne. Nutrient deficiency may cause physiological and metabolism abnormalities in plants, which may lead to deficiency symptoms.…”
Section: Nutrient Availabilitymentioning
confidence: 99%
“…The ability to acquire P from the soil and use it efficiently for biomass production is an important characteristic for adaptation to soils low in available P (Pang et al 2010). In general, at lowmedium P levels, T. subterraneum was the most efficient species in utilizing applied P for biomass production (P required g…”
Section: P Efficiencymentioning
confidence: 99%
“…One of the major mechanisms that plants have evolved to overcome low-P availability is to maximize the ability of the roots to acquire and absorb P from the soil. Plants can mobilize P through the exudation of organic acids, acid phosphatases, and ribonucleases, resulting in enhanced P availability and uptake (Hinsinger, 2001;Ryan et al, 2001;Dakora and Phillips, 2002;Hammond and White, 2008;Ma et al, 2009;Pang et al, 2009). Another strategy to cope with low-P availability is to increase the soil volume accessed by root systems by forming mycorrhizal symbioses Smith and Smith, 2012;Rai et al, 2013).…”
mentioning
confidence: 99%